2015
DOI: 10.1071/rd14009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different freezing velocities on the quality and fertilising ability of cryopreserved rabbit spermatozoa

Abstract: The freezing step of the cryopreservation protocol negatively influences the quality and fertilising ability of rabbit spermatozoa. This study determines the effect of different rates of freezing on the quality and fertilising ability of rabbit spermatozoa cryopreserved with dimethylsulfoxide (DMSO) (1.75M) and sucrose (0.05M). Ejaculates from meat rabbit line males (n=12) were pooled and each pool (n=7) was split into four aliquots. One group of straws (control, C) was frozen in static liquid nitrogen vapour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…Semen characteristics after the freezing-thawing procedures are summarized in Table1, where the dramatic reduction of sperm motility (Rmot=83%) and normal acrosome status (Rnar=74%) can be observed. For Mot-FT, Nar-FT and Live-FT, the means obtained are lower than the values reported for the same line in studies in which the ejaculates are preselected for cryopreservation [8,12]. Important differences of the present study were the assessment of individual, rather than pooled ejaculates, and the lack of ejaculates pre-selection before freezing.…”
Section: Resultscontrasting
confidence: 81%
See 1 more Smart Citation
“…Semen characteristics after the freezing-thawing procedures are summarized in Table1, where the dramatic reduction of sperm motility (Rmot=83%) and normal acrosome status (Rnar=74%) can be observed. For Mot-FT, Nar-FT and Live-FT, the means obtained are lower than the values reported for the same line in studies in which the ejaculates are preselected for cryopreservation [8,12]. Important differences of the present study were the assessment of individual, rather than pooled ejaculates, and the lack of ejaculates pre-selection before freezing.…”
Section: Resultscontrasting
confidence: 81%
“…The percentage of viable (plasma membrane intact) sperm (Live-FT, %) in each frozen-thawed sample was determined using flow cytometry, as described by Mocé et al [12]. Briefly, a sample from each thawed straw was diluted with Tris-BSA to 30 x 10 6 sperm/ mL.…”
Section: Semen Evaluation and Traitsmentioning
confidence: 99%
“…The ice crystal formation during the freezing process damage cells as described above and freezing protocol is also one of the concerns. In rabbit sperms, it was revealed that sperms frozen at slow (−15 °C/min) and fast (−60 °C/min) rates were lower in the quality and fertilizing ability than those frozen at medium (−40 °C/min) rate and in static liquid nitrogen vapor [ 52 ].…”
Section: Effects Of Freezing and Thawing Proceduresmentioning
confidence: 99%
“…Sperm concentration and morphology were evaluated for fresh semen samples, whereas motility (percent total and progressively motile sperm, determined using Computer Assisted Sperm Analyzer system) and plasma membrane integrity (live sperm, determined using flow cytometry for sperm stained with SYBR-14 and propidium iodide) were determined for both fresh and cryopreserved sperm as described by Mocé et al [10].…”
Section: Experimental Designmentioning
confidence: 99%
“…Frozen-thawed sperm were inseminated into receptive females using the protocol described by Mocé et al [10]. At parturition, number of young born alive, the number of fetal deaths, and the total number of kits born (number of alive þ number of dead) for each female were determined.…”
Section: Experiments 2 Effect Of Equilibration Time At 5 C On the Quamentioning
confidence: 99%